Feedback, task performance, and interface preferences. Issue 6 (2nd November 2018) - Bellman, Steven; Murray, Kyle B.
ABSTRACT: Interface preferences are influenced by switching costs, including cognitive switching costs of thinking and task performance. In this research, we use feedback intervention theory to predict that feedback can have psychological effects that override the lock-in effect of cognitive switching costs on interface preference. To demonstrate this effect, we use normative feedback, which compares a user's task performance to the performance of others. This focuses attention on the user's self-concept and away from task performance. We use a hedonic information systems (IS) interface – an online game – as feedback valence should have a stronger effect on preferences for hedonic IS as opposed to utilitarian IS. Hedonic IS are preferred for their enjoyment value, as well as their productivity, and positive feedback should be more enjoyable than negative feedback. Results from an online experiment that manipulated the presence of feedback and feedback valence, for a sample of 482 users, support our hypotheses. The theoretical and managerial implications of these results are discussed.